The onset and the development of cardiometabolic aging: an insight into the underlying mechanisms - Sarkar, Sulogna; Prasanna, Vani S.; Das, Pamelika; Suzuki, Hiroshi; Fujihara, Kazuya; Kodama, Satoru; Sone, Hirohito; Sreedhar, Remya; Velayutham, Ravichandiran; Watanabe, Kenichi; Arumugam, Somasundaram (Frontiers in Pharmacology, 2024)
Metabolic compromise is crucial in aggravating age-associated chronic inflammation, oxidative stress, mitochondrial damage, increased LDL and triglycerides, and elevated blood pressure. Excessive adiposity, hyperglycemia, and insulin resistance due to aging are associated with elevated levels of damaging free radicals, inducing a proinflammatory state and hampering immune cell activity, leading to a malfunctioning cardiometabolic condition. The age-associated oxidative load and redox imbalance are contributing factors for cardiometabolic morbidities via vascular remodelling and endothelial damage. Recent evidence has claimed the importance of gut microbiota in maintaining regular metabolic activity, which declines with chronological aging and cardiometabolic comorbidities. Genetic mutations, polymorphic changes, and environmental factors strongly correlate with increased vulnerability to aberrant cardiometabolic changes by affecting key physiological pathways. Numerous studies have reported a robust link between biological aging and cardiometabolic dysfunction. This review outlines the scientific evidence exploring potential mechanisms behind the onset and development of cardiovascular and metabolic issues, particularly exacerbated with aging.